Canada : 2019 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2019)
Growth has slowed to a more sustainable level and financial vulnerabilities have eased. But risks remain. Household debt is high, the United States-Mexico-Canada Agreement (USMCA) awaits legislative approval, and ongoing trade tensions between the United States (U.S.) and its major trading partners are weighing on the global outlook.